Invasive disease-free and overall survival after (neo)adjuvant chemotherapy in postmenopausal patients with hormone receptor-positive, HER2-negative early breast cancer treated with upfront letrozole: experiences from the phase IV PreFace trial - Beierlein, Milena; Häberle, Lothar; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans-Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (International journal of cancer, 2025)
Patients with hormone receptor-positive (HRpos), HER2-negative (HER2neg) breast cancer (BC) benefit less from neoadjuvant chemotherapy (NACT) than patients with triple-negative and HER2-positive BC. In this retrospective analysis of the phase IV PreFace clinical trial (NCT01908556), where postmenopausal HRpos BC patients (n = 3297) were treated with 5-year upfront adjuvant letrozole therapy, we evaluated the prognosis of patients treated with adjuvant versus neoadjuvant chemotherapy in HRpos/HER2neg early-stage BC. HRpos/HER2neg patients with information on (neo)adjuvant chemotherapy (n = 2895) were retrospectively selected from all patients enrolled in the PreFace trial. Invasive disease-free survival (iDFS) and overall survival (OS) were compared between patient groups that were treated with neoadjuvant or adjuvant chemotherapy. Chemotherapy was given to 1051 patients (36.3% of all patients), of which 874 (83.2%) received adjuvant chemotherapy and 177 (16.8%) NACT. Pathologic complete response (pCR) rate in the NACT group was 6.9%. Patients treated with NACT had a worse outcome than those treated with adjuvant chemotherapy (5-year iDFS rate 81% vs. 88%; 5-year OS rate 89% vs. 93%). This effect was maintained after adjusting for age, BMI, lymph node status, grading, tumor size, and histology (hazard ratio for iDFS: 1.95 (95%CI: 1.28-2.95); hazard ratio for OS: 2.13 (95%CI: 1.24-3.66)). Further adjustment for taxane-based regimes did not alter results. In conclusion, in this retrospective analysis of patients with early-stage HRpos/HER2neg BC, patients with NACT had a more unfavorable prognosis than patients treated adjuvantly, independent of patient and tumor characteristics. Prognosis of neoadjuvant patients might be affected by resistance mechanisms, warranting further investigation.